2019
DOI: 10.20944/preprints201901.0313.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Steroid Receptors and Vertebrate Evolution

Abstract: Considering that life on earth evolved about 3.7 billion years ago, vertebrates are young, appearing in the fossil record during the Cambrian explosion about 542 to 515 million years ago.  Results from sequence analyses of genomes from bacteria, yeast, plants, invertebrates and vertebrates indicate that receptors for adrenal steroids (aldosterone, cortisol), and sex steroids (estrogen, progesterone, testosterone) also are young, with receptors for estrogens and 3-ketosteroids first appearing in basal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 72 publications
(121 reference statements)
0
3
0
Order By: Relevance
“…C. elegans worms share hormones such as estrogen and oxytocin with humans but do not possess cortisol [ 12 , 13 , 16 , 24 ]. However, pregnenolone, a precursor of many steroid hormones, is present in C. elegans and has been found to prolong C. elegans lifespan [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. elegans worms share hormones such as estrogen and oxytocin with humans but do not possess cortisol [ 12 , 13 , 16 , 24 ]. However, pregnenolone, a precursor of many steroid hormones, is present in C. elegans and has been found to prolong C. elegans lifespan [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although C. elegans possesses some steroid hormone signaling molecules, such as estrogen and dafachronic acid, the full spectrum of cortisol effects in C. elegans is unclear [ [13] , [14] , [15] ]. Furthermore, a previous molecular evolution study suggested that invertebrates do not have GRs [ 16 ]. Nevertheless, C. elegans has been reported to possess DHS-30, an ortholog of human dehydrogenase/reductase SDR family member 7B (DHRS7B), which affects steroid hormone synthesis, and the ACTH-releasing hormone receptor SEB-3 [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen receptor subtypes emerged in cartilaginous fishes (Chondrichthyes like sharks), which have skeletons composed of cartilage rather than bone. This duplication of the receptors promoted the diversification of signaling by estrogens that readily diffuse through cell membranes [ 65 , 66 , 67 ]. As mentioned above for zebrafish, the teleost lineage has at least three estrogen receptors, esr1 (α subtype), esr2b , and esr2a (β subtypes), which are the results of a whole genome duplication that occurred in the evolution of this lineage [ 68 , 69 , 70 ].…”
Section: Estrogen Receptors In Oviparous Vertebrates and Their Hepatic Expressionmentioning
confidence: 99%